2008
DOI: 10.1177/000348940811700202
|View full text |Cite
|
Sign up to set email alerts
|

How does Cricotracheal Resection Affect the Female Voice?

Abstract: Cricotracheal resection can significantly impact the adult female voice. It often lowers the pitch of the speaking voice into the male range and reduces the pitch range of the voice. The change in voice that potentially accompanies this procedure should be discussed with patients in preoperative counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(92 citation statements)
references
References 20 publications
5
86
1
Order By: Relevance
“…Only one study with 32 patients quantified voice outcome from good to poor (25). Patients, especially (young) female patients, can experience a deeper voice after surgery as a serious handicap (9,27). As shown in our current study, voice dysfunction is indeed an existing and a relevant problem, especially after LTR.…”
Section: Discussionmentioning
confidence: 50%
“…Only one study with 32 patients quantified voice outcome from good to poor (25). Patients, especially (young) female patients, can experience a deeper voice after surgery as a serious handicap (9,27). As shown in our current study, voice dysfunction is indeed an existing and a relevant problem, especially after LTR.…”
Section: Discussionmentioning
confidence: 50%
“…Indeed these inherently biomechanical variations of vocal fold tissues might facilitate the transfer of energy from the subglottal airflow to the mucosal wave. 26,44,45 One finding (Fig. 4) that differs from Goodyer et al 26 is that the variations of mass and stiffness from inferior to superior along the vertical direction are not totally linear.…”
Section: Distribution Of Local Effective Mass and Stiffnessesmentioning
confidence: 83%
“…Smith et al in a study of 14 females who underwent CTR found the fundamental frequency dropping by 21Herz (Hz) (p=0.03) in the post-operative period (12). However, the post-operative recordings were taken at different intervals (2.4-5.2 months) and the patients had a mixture of CTR techniques with varying degree of cricoid resection.…”
Section: Voicementioning
confidence: 98%
“…Common voice problems post-surgery include lower pitch, huskiness, difficulties with projection, vocal fatigue and inability to sing (10,12). Cricotracheal resection, in particular, is understood to alter female voices and can bring their vocal profile into a male range.…”
Section: Voicementioning
confidence: 99%